Legal Certainty The Obligation To Make Administrative Efforts Before Filing A Lawsuit In The Administrative Court - Raya, Bonifacius (Green Publisher Indonesia, 2024)
In accordance with the provisions of Article 48 of Law Number 5 of 1986 concerning the State Administrative Court which has been last amended by Law Number 51 of 2009 concerning the Second Amendment of Law Number 5 of 1986 concerning the State Administrative Court (